The associations among serum vitamin D concentration, systemic immune-inflammation index, and lifestyle factors in Chinese adults: a cross-sectional analysis - Chan, Feiin; Cui, Chongsong; Peng, You; Liu, Zhenjie (Frontiers in Nutrition, 2025)
IntroductionVitamin D is a crucial lipid-soluble hormone that has been demonstrated to be closely associated with systemic chronic inflammation and various diseases, including metabolic disorders, cardiovascular conditions, autoimmune diseases, cancer, and aging. The pathological underpinnings of these diseases are intricately linked to systemic chronic inflammation. The systemic immune-inflammation index (SII), an emerging biomarker, offers a more comprehensive reflection of the state of systemic inflammation and the immune response by integrating interactions among diverse immune cell types. This study aimed to evaluate the association between serum 25-hydroxyvitamin D (25(OH)D) concentrations and the SII while further exploring the association between vitamin D levels and systemic chronic inflammation in the Chinese population. Additionally, it analyses how lifestyle choices and dietary habits influence vitamin D levels.MethodologyThis investigation employed a cross-sectional research design involving 1,177 participants aged 18–90 years who were selected from Zhong Hospital in Guangdong Province, China, through screening procedures. Ultimately, data from 726 participants were analysed following the screening and inclusion criteria. The participants were categorized into three groups on the basis of their serum vitamin D concentrations: the deficient group (SVD < 20 ng/mL), suboptimal group (SVD ≥ 20 but<30 ng/mL), and optimal group (SVD ≥ 30 ng/mL). Physiological indicators, medical history, lifestyle and dietary habits were collected; the SII was calculated via the following formulas: SII=platelet count×neutrophil count/lymphocyte count. Statistical comparisons of the intergroup differences were subsequently conducted, followed by logistic regression and correlation analyses. Subsequently, intergroup differences were assessed, and logistic regression and correlation analysis were performed.ResultsThe findings indicated that the SII value in the vitamin D-deficient group was significantly higher than that in the optimal group (p < 0.05). Furthermore, individuals in this deficient category presented elevated levels of metabolic markers such as total cholesterol, low-density lipoprotein cholesterol (LDL-C), fasting blood glucose, glycated hemoglobin A1c (HbA1c), and uric acid alongside unhealthy lifestyle practices characterized by frequent consumption of cold foods and sugary beverages coupled with high work-related stressors and prolonged air conditioning use (p < 0.05). Conversely, high-density lipoprotein cholesterol (HDL-C) was positively correlated with vitamin D status (p < 0.05).ConclusionThese results substantiate the association between vitamin D levels and the SII while suggesting that interventions targeting lifestyle modifications may positively impact vitamin D status, thereby ameliorating systemic chronic inflammation. Although this study provides preliminary evidence regarding the interplay between vitamin D deficiency and systemic inflammatory processes, further investigations are warranted to elucidate the underlying biological mechanisms and explore potential strategies for regulating vitamin D concentrations through improved lifestyles and dietary choices.